An acute naproxen dose does not affect core temperature or Interleukin-6 during cycling in a hot environment - Dawn M. Emerson; Stephen CL. Chen; Toni M. Torres-McGehee; Craig E. Pfeifer; Charles C. Emerson; J. Mark Davis (Sports Medicine and Health Science, 2021)
Non-steroidal anti-inflammatory drugs’ anti-pyretic and anti-inflammatory effects has led some individuals to theorize these medications may blunt core body temperature (Tc) increases during exercise. We utilized a double-blind, randomized, and counterbalanced cross-over design to examine the effects of a 24-h naproxen dose (3–220 ​mg naproxen pills) and placebo (0 ​mg naproxen) on Tc and plasma interleukin-6 (IL-6) concentrations during cycling in a hot or ambient environment. Participants (n ​= ​11; 6 male, 5 female; age ​= ​27.8 ​± ​6.5 years, weight ​= ​79.1 ​± ​17.9 ​kg, height ​= ​177 ​± ​9.5 ​cm) completed 4 conditions: 1) placebo and ambient (Control); 2) placebo and heat (Heat); 3) naproxen and ambient (Npx); and 4) naproxen and heat (NpxHeat). Dependent measures were taken before, during, and immediately after 90 ​min of cycling and then 3 ​h after cycling. Overall, Tc significantly increased pre- (37.1 ​± ​0.4 ​°C) to post-cycling (38.2 ​± ​0.3 ​°C, F1.7,67.3 ​= ​150.5, p ​< ​0.001) and decreased during rest (37.0 ​± ​0.3 ​°C, F2.0,81.5 ​= ​201.6, p ​< ​0.001). Rate of change or maximum Tc were not significantly different between conditions. IL-6 increased pre- (0.54 ​± ​0.06 ​pg/ml) to post-exercise (2.46 ​± ​0.28 ​pg/ml, p ​< ​0.001) and remained significantly higher than pre-at 3 ​h post- (1.17 ​± ​0.14 ​pg/ml, 95% CI ​= ​−1.01 to −0.23, p ​= ​0.001). No significant IL-6 differences occurred between conditions. A 24-h, over-the-counter naproxen dose did not significantly affect Tc or IL-6 among males and females cycling in hot or ambient environments.